2023
DOI: 10.3389/fonc.2022.1049531
|View full text |Cite
|
Sign up to set email alerts
|

Conditional survival analysis and real-time prognosis prediction for cervical cancer patients below the age of 65 years

Abstract: BackgroundSurvival prediction for cervical cancer is usually based on its stage at diagnosis or a multivariate nomogram. However, few studies cared whether long-term survival improved after they survived for several years. Meanwhile, traditional survival analysis could not calculate this dynamic outcome. We aimed to assess the improvement of survival over time using conditional survival (CS) analysis and developed a novel conditional survival nomogram (CS-nomogram) to provide individualized and real-time progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In this study, we utilized the least absolute shrinkage and selection operator (LASSO) regression technique with 10-fold cross-validation to identify independently prognostic factors in the training cohort [16]. Subsequently, multivariate Cox regression was conducted to con rm the prognostic value of the selected variables and integrate them into a new nomogram model [17]. The CS concept was nally utilized in the development of a CS-nomogram, which is capable of providing personalized, real-time prognostic information that is continually updated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we utilized the least absolute shrinkage and selection operator (LASSO) regression technique with 10-fold cross-validation to identify independently prognostic factors in the training cohort [16]. Subsequently, multivariate Cox regression was conducted to con rm the prognostic value of the selected variables and integrate them into a new nomogram model [17]. The CS concept was nally utilized in the development of a CS-nomogram, which is capable of providing personalized, real-time prognostic information that is continually updated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we computed the total count and percentage of categorical variables in the entire cohort, training cohort, and validation cohort. CS(y|x) is the probability of additional y years of survival given that the patient has not died of MCC by a speci c period of time (x years) after initial diagnosis [14]. Standard de nition of conditional probability was used to calculate CS: CS(y|x) = OS(y + x)/OS(x).…”
Section: Discussionmentioning
confidence: 99%
“…The ROC curves remained stable over a period of 3, 5, and 10 years. Finally, we evaluated the e cacy of this model in the healthcare system, and our survival prognostication model demonstrated superior cumulative bene t and greater robustness to survival probabilities via DCA analysis [31,32]. This indicated that our model demonstrated outstanding predictive performance and clinical applicability, providing patients with greater overall bene ts and aiding physicians in making treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized the least absolute shrinkage and selection operator (LASSO) regression technique with 10-fold cross-validation to identify independently prognostic factors in the training cohort ( 17 ). Subsequently, multivariate Cox regression was conducted to confirm the prognostic value of the selected variables and integrate them into a new nomogram model ( 18 ). The CS concept was finally utilized in the development of a CS-nomogram, which is capable of providing personalized, dynamic prognostic information that is continually updated.…”
Section: Methodsmentioning
confidence: 99%